2012
DOI: 10.1590/s0036-46652012000600003
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of human bocavirus respiratory infections among at-risk patients in São Paulo, Brazil

Abstract: SUMMARYBackground and objectives: Human Bocavirus (HBoV) has been described since 2005 as an etiological agent of respiratory virus infections. From 2001 to 2008 we investigated the etiology of HBoV among adults and children in different groups at risk of presenting complications arising from acute respiratory infection, the investigation was carried out in a tertiary hospital health care system in Brazil. Methods: HBoV DNA was assayed in 598 respiratory samples from community and hospitalized patients by PCR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
2
7
0
3
Order By: Relevance
“…In the Netherlands, the hypovolemic shock has been reported due to diarrhea associated with disseminated HBoV infection in an immunocompromised child after liver and allogeneic hematopoietic stem cells transplantation . In Brazil, the frequency of HBoV was reported in 0.4% of patients transplanted from bone marrow …”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, the hypovolemic shock has been reported due to diarrhea associated with disseminated HBoV infection in an immunocompromised child after liver and allogeneic hematopoietic stem cells transplantation . In Brazil, the frequency of HBoV was reported in 0.4% of patients transplanted from bone marrow …”
Section: Introductionmentioning
confidence: 99%
“…En Argentina se ha estudiado la prevalencia de HBoV en la provincia de Córdoba, donde obtuvieron resultados entre 6,8 y 27,3% desde 2007 a 2011 14,17 ; y en Buenos Aires, donde el virus se encontró en porcentajes que variaron entre 10,8 y 18,4%, entre los años 2007 y 2010 24,25 . En lo que respecta al resto de América Latina, en Brasil trabajos reportan 2,44% de prevalencia 15 ; en Chile 21,8% 22 ; en Perú, 25,1% 24 y en Nicaragua, 33,3% 24 . El amplio rango de frecuencia con que se detecta el genoma de HBoV, podría deberse a las variaciones en la elección de la secuencia blanco y/o de la metodología.…”
Section: Discussionunclassified
“…Los porcentajes de positividad en ambas provincias fueron ligeramente superiores en los meses correspondientes a las estaciones de primavera y verano. Si bien la mayoría de los autores reportó tasas superiores del virus en los meses de otoño e invierno [13][14][15]17,22 , estudios realizados en China 7,19 muestran una mayor frecuencia de HBoV en los meses de primavera y verano. Zhou y cols., realizaron un estudio durante tres años y hallaron tasas más elevadas en los meses de verano 19 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…In HBoV (+) LRTI group, to have an ill subling with similar symptoms and number of sublings (≥3 or more) were found to be risk factors. In one of study, Caccia et al 18 reported that HBoV positivity was found in children with respiratory infections who had underlying risk factors as heart disease. In another study, maternal smoking and being born in winter season were found to be associated with HBoV infection 19 .…”
Section: Discussionmentioning
confidence: 99%